Pengaruh Kinerja Lingkungan , Umur Perusahaan, dan Dewan Pengawas Sya’riah Terhadap Islamic Social Reporting (ISR) (Jurnal Kendali Akuntansi, 2024)
The purpose of this study is to determine the effect of environmental performance, independent commissioners, company age and sharia supervisory board on Islamic social reporting in Islamic banking in Indonesia. The research time period used is 5 years, namely the 2017-2021 period. The population of this study includes all Islamic banking registered with the Financial Services Authority (OJK) in the form of Sharia Commercial Banks (BUS) for the 2017-2021 period. The sampling technique used purposive sampling technique. Based on the criteria that have been defined as 10 companies. The type of data used is secondary data obtained from the website of the Financial Services Authority (OJK). The analytical method used is panel data regression analysis. The results show that partially environmental performance has a positive effect on ISR, independent commissioners of company age and sharia supervisory boards have no effect on ISR.